ADOPTING AHP IN EVALUATING NURSE SCHEDULING METHODS - Razamin Ramli; Adli Mustafa; Ahamad Tajudin Khader (Program Studi Statistika Unisba, 2004)
When comparing and evaluating two or more scheduling methods the need to use a multiple criteria decisionmakingtechnique arises. Instead of just employing a qualitative approach of evaluating the methods, one can integrate thequalitative and the quantitative data in the evaluation process through the use of the analytic hierarchy process (AHP).Hence, this paper reports the evaluation of two nurse scheduling methods where the AHP technique is employed to supportthe selection process of these methods. Five decision criteria are used in the process. The main objective of the schedulingmethods (models) is to assign work shifts and off days of the nurses in a particular hospital unit such that, it fulfils certainspecified constraints while ensuring continuous high-quality patient care services. The first method is a heuristic procedurethat is currently in practice. The other one is a prototype in which a memetic algorithm is adopted in the approach. Theapplication of AHP has been found to provide a better transparency of the capability and efficiency of the schedulingmethods. Consequently, the memetic algorithm approach stands out to be the better one based on the evaluation scheme.